Microscopic Polyangiitis: New Insights into Pathogenesis, Clinical Features and Therapy - Karras, Alexandre (Seminars in Respiratory and Critical Care Medicine, 2018)
Microscopic polyangiitis (MPA) is one of the main clinical presentations of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitides. Although the disease is defined by clinical and pathological criteria, the anti-myeloperoxidase (MPO) specificity of ANCAs is observed in almost 80% of MPA patients. The direct pathogenic role of anti-MPO antibodies has been proven in animal models, in which the disease was transmitted by transfer of anti-MPO antibodies or anti-MPO–specific splenocytes. The most frequently affected organs in this disease are the kidneys and the lungs. Necrotizing and crescentic glomerulonephritis can be revealed by rapidly progressive renal failure, but kidney injury can be more slowly progressive and lead to end-stage renal disease without major extrarenal manifestations. The most frequent pulmonary manifestation is diffuse alveolar hemorrhage, but some patients may present with chronic interstitial fibrosis leading to respiratory failure. General signs such as fever and weight loss, muscular and articular symptoms, peripheral neuropathy, and cutaneous involvement may also reveal the disease. Although the relapse rate is quite low after induction of remission, 5-year mortality is 25%, with even higher mortality rates in older patients (> 65 years old), or those with significant kidney dysfunction. Iatrogenic causes (particularly infections) are an important cause of deaths in these vulnerable patients. Future studies are warranted to determine the optimal maintenance immunosuppressive regimen to minimize side effects of immunosuppression.
Keywords: vasculitis; anti-myloperoxydase; ANCA; glomerulonephritis; lung fibrosis